ANALISIS PENGARUH CORPORATE TAX, LEVERAGE EFFECT, RISKY DEBT, MULTIACTIVITY FIRM DAN DEGREE OF OPERATING LEVERAGE TERHADAP SYSTEMATIC RISK PADA PERUSAHAAN NON-KEUANGAN KOMPAS100 TAHUN 2010-2015 - Lumbanradja, Ramos; Arfinto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2016)
This Research aimed to analyze the influence of Corporate Tax, Leverage Effect, Risky Debt, Multiactivity Firm and Degree Of Operating Leverage to Systematic Risk. Case study on non-financial company in KOMPAS100 during the period 2010- 2015. By using purposive sampling method obtained a sample of 22 companies. Company data used in this study was obtained from the Indonesian Capital Market Directory for 2010-2015 and www.bloomberg.com. The analysis technique used is Ordinary Least Squares Regression (OLS). The results showed only a Corporate Tax which has positive and not significant against Systematic Risk. Leverage Effect, Risky Debt and Multiactivity Firm which has positive and significant against Systematic Risk, while DOL does not affect the Market Value Added.